2016
DOI: 10.1080/21645515.2016.1197451
|View full text |Cite
|
Sign up to set email alerts
|

Other age groups than children need to be considered as carriers of Streptococcal pneumoniae serotypes

Abstract: We need to raise the issue that focus on children as the only carriage group for pneumococci is not optimal; we need to consider that other age groups might also be carriers of pneumococcal serotypes causing invasive pneumococcal diseases (IPD) in unvaccinated age groups. The pneumococcal conjugate vaccines (PCV) have successfully removed IPD from vaccinated children. Studies have shown an effect of PCV reducing the pneumococcal carriage of PCV serotypes in children. The status for several countries having use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…1 ) and by others 7 , 20 , 22 , 34 . Despite the use of effective vaccines, serotypes 3, 7F and 19A, which are included in PCV13, are still causing IPD among elderly in Denmark 13 , 14 (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) and by others 7 , 20 , 22 , 34 . Despite the use of effective vaccines, serotypes 3, 7F and 19A, which are included in PCV13, are still causing IPD among elderly in Denmark 13 , 14 (Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCV7 includes serotype 4, 6B, 9V, 14, 18C, 19F, and 23F while PCV13 includes the PCV7-serotypes and additional serotypes 1, 3, 5, 6A, 7F, and 19A 1 , 7 . PCV7 led to a significant reduction in IPD caused by PCV7-serotypes markedly among children aged <2 years 1 , 3 , 6 , 13 , but also a significant reduction in IPD cases and carriage of vaccine serotypes among older children and adults was seen, especially in the age group 65+ years 3 , 8 . This phenomenon is known as herd protection 8 .…”
Section: Introductionmentioning
confidence: 94%
“…Despite the qPCR-based method being reported as one of the most sensitive for serotype detection in polymicrobial samples 45 , this study demonstrates the need for further expansion of reliable assays. Broader serotype coverage is essential for accurate pneumococcal surveillance in this post-vaccination era, particularly when adult pneumococcal vaccination is considered 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The focus in recent years has therefore turned to predicting which non-vaccine IPD serotypes will emerge (serotype replacement) and several studies from around the world have shown data on the most common non-PCV serotypes in their region [3, 8]. However, as has also been observed in several studies [13], PCV-13 has not had an equal effect for the thirteen serotypes covered by the vaccine, and in Denmark the current situation is that serotype 3 is still a common cause of IPD in the elderly. On the recent pneumococcal meeting (ISPPD-10) in Glasgow, several countries reported a similar situation, with increasing IPD incidences caused by some of the PCV-13 serotypes in the non-vaccinated age groups, including serotypes 3 and 19A [14, 15, 16, 17].…”
Section: Discussionmentioning
confidence: 99%